Computations with Modular Forms: Proceedings of a Summer School and Conference, Heidelberg, August/September 2011 - Böckle, Gebhard (Contributions in Mathematical and Computational Sciences, 2014)
Part I Summer School: Lectures on Computing Cohomology of Arithmetic Groups by P.E. Gunnells -- Computing with Algebraic Automorphic Forms by D. Loeffler -- Overconvergent Modular Symbols by R. Pollack -- Part II Conference and Research Contributions: Congruence Subgroups, Cusps and Manin Symbols over Number Fields by J. E. Cremona and M. T. Aranés -- Computing Weight One Modular Forms over C and Fp by K. Buzzard -- Lattice Methods for Algebraic Modular Forms on Classical Groups by M. Greenberg and J. Voight -- Efficient Computation of Rankin p-Adic L-Functions by A.G.B. Lauder -- Formes Modulaires Modulo 2 et Composantes Réelles de Jacobiennes Modulaires by L.Merel -- Universal Hecke L-Series Associated with Cuspidal Eigenforms over Imaginary Quadratic Fields by A. Mohamed -- On Higher Congruences Between Cusp Forms and Eisenstein Series by B. Naskrecki -- Arithmetic Aspects of Bianchi Groups by M.H.Sengün -- A Possible Generalization of Maeda’s Conjecture by P. Tsaknias -- Computing Power Series Expansions of Modular Forms by J. Voight and J. Willis -- Computing Modular Forms for GL2 over Certain Number Fields by D. Yasaki